The explicit mentioning of reporting guidelines in urogynecology journals in 2013: A bibliometric study. Issue 3 (24th January 2015) - Koch, Marianne; Riss, Paul; Umek, Wolfgang; Hanzal, Engelbert
Abstract : Aims: Poor reporting of research may limit critical appraisal and reproducibility, whereas adherence to reporting guidelines (RG) can guarantee completeness and transparency. We aimed to determine the explicit citing of RGs (CONSORT, PRISMA, STROBE) in urogynecology articles in 2013, the requirements of relevant journals and a potential difference between urogynecology and general gynecology journals. Methods: All urogynecologic articles published between January and December 2013 in the journals NAU, IUJ, FPMRS, GREEN, AJOG, and BJOG were included. Issues were searched for systematic reviews, RCTs, cohort studies, case‐control studies and cross‐sectional studies. Each electronic article was searched for the term PRISMA, CONSORT, or STROBE according to the study design. Instructions to Authors of the six journals were screened for requirement of using RGs. Results: We included 296 articles (243 observational studies, 40 RCTs, and 13 systematic reviews). The use of PRISMA guidelines was explicitly declared in 54% of systematic reviews, CONSORT guidelines were referenced in 25% of RCTs and STROBE in 1.2% of observational studies. The use of CONSORT is required by all journals except FPMRS. PRISMA and STROBE are only compulsory in the journals GREEN, AJOG, and BJOG. The overall rate of explicit mentioning of RGs comparing urogynecology and general gynecology journals was 6.7% versus 7.1%, respectively. Conclusions: The explicit mentioning of RGs was on a relatively low level. A slightly higher adherence was recognized among general gynecology journals compared to urogynecology journals. Stronger efforts should be taken to further promote the use of RGs in urogynecology. Neurourol. Urodynam. 35:412–416, 2016 . © 2015 Wiley Periodicals, Inc.